2016
DOI: 10.3390/nu8070431
|View full text |Cite
|
Sign up to set email alerts
|

Quercitrin from Toona sinensis (Juss.) M.Roem. Attenuates Acetaminophen-Induced Acute Liver Toxicity in HepG2 Cells and Mice through Induction of Antioxidant Machinery and Inhibition of Inflammation

Abstract: Quercitrin is found in many kinds of vegetables and fruits, and possesses various bioactive properties. The aim of the present study was to elucidate hepatoprotective mechanisms of quercitrin isolated from Toona sinensis (Juss.) M.Roem. (syn. Cedrela sinensis Juss.), using acetaminophen (APAP)-treated HepG2 cell and animal models. In an in vitro study, quercitrin suppressed the production of reactive oxygen species and enhanced expression of nuclear factor E2-related factor 2 (Nrf2), activity of antioxidant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“… 7 days Balb/c mice, 300 mg/kg i.p. ↓Oxidative stress, inflammation [112] Caffeic acid 10–30 mg/kg p.o. 7 days ICR mice, 400 mg/kg p.o.…”
Section: Targeting Mitochondrial Oxidative Stress and Dysfunction Formentioning
confidence: 99%
See 1 more Smart Citation
“… 7 days Balb/c mice, 300 mg/kg i.p. ↓Oxidative stress, inflammation [112] Caffeic acid 10–30 mg/kg p.o. 7 days ICR mice, 400 mg/kg p.o.…”
Section: Targeting Mitochondrial Oxidative Stress and Dysfunction Formentioning
confidence: 99%
“… Balb/c mice, 300 mg/kg i.p. ↑SOD, CAT and GPx; ↓inflammation [112] Methanol extract of pomegranate peels 50 mg/kg p.o. for 14 days Wistar rats, 750 mg/kg i.p.…”
Section: Targeting Mitochondrial Oxidative Stress and Dysfunction Formentioning
confidence: 99%
“…In addition, another investigation in 2012 reported that TSL could ameliorate the antioxidant enzymes activity in H 2 O 2 induced oxidative rats liver which would be beneficial for the hepatic detoxification (Yu et al, 2012). Recently, Truong et al (2016) reported that the quercitrin extracted from the T. sinensis attenuated acetaminophen-induced acute liver toxicity in HepG2 Cells and mice, and the related mechanisms is correlated to activating defensive genes and inhibiting pro-inflammatory mediators via suppressing JNK and p38 pathway.…”
Section: Hepatoprotective Effectmentioning
confidence: 99%
“…They mainly refer to two benzene rings (A ring and B ring) as the mother nucleus, which are linked by a central three carbon chain (C chain). The series of compounds with the C6-C3-C6 basic carbon skeleton contain a plurality of hydroxyl groups (OH) and are highly polar [6, 7]. The basic structure is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%